Synthesis and Antibacterial Activity of bis Heterocyclic Derivatives of 1,3,4-thiadiazole - Ahlam A. Al-jubouri; Ahlam J. Qasir (College of Pharmacy University of Baghdad, 2017)
The Chemistry of heterocyclic sulphur and nitrogen containing compounds have a great role in the  field of scientific studies, The 2-amino 5-mercapto-1,3,4-thiadiazole ring for instance, has gained more importance in recent years because  they are considered as potent biologically active nucleus. In this study disulfide derivative can be obtained by oxidation with hydrogen peroxide of thiol group of the heterocyclic 2-amino 5-mercapto-1,3,4-thiadiazole ring to obtain compound (3) with expected antibacterial  activity. In order to use it as a diazo component to prepare some new bis azo compounds as possible antibacterial  agents, the reaction of two primary amino groups on both sides of disulfide dimer with sodium nitrite was carried out to prepare diazounium salt which was coupled with different coupling compounds to form the azo linkage. The reaction steps and the purity of the products were confirmed by thin layer chromatography (TLC) and melting points measurement .The chemical structure of the final compounds were characterized and confirmed by measuring their FT-IR spectroscopy and elemental microanalysis(C, H, N &S).These compounds were screened for their antibacterial activity which was done on four different strains of bacteria by well diffusion method. These compounds show moderate to good activity against tested gram positive bacteria and low or no activity against gram negative bacteria compared to the standard compounds. Key words: Disulfide dimer, Diazo compound, Antibacterial  activity.